Direct Investment, Economic Integration and the Welfare State: The Case of European Integration - Torben Dall Schmidt (European Regional Science Association (ERSA), 2001)
It has been argued, that economic integration casts serious doubts on the efficiency of welfare state policies and the ability to finance these. As integration proceeds, factors of production become more mobile and less vulnerable to local shocks, and integration at the same time results in a footloose tax base - all effects pointing to the death of the welfare state. Recent advances in European integration has especially added to the mobility of capital. Using direct investment activities as a benchmark, the present paper explores potential effects of a number of mechanisms, that may critially alter the conclusions on economic integration. These mechanisms include such aspects as risk diversification risk-shifting and elastic local returns - aspects that are vital in answering questions on the efficiency of welfare state activities and questions on the ability to finance these activities in an international setting with the potential of shifting the tax burden abroad. The results indicate that the situation may indeed be less critical for the welfare state, than expected from ''traditional" arguments.
Keywords: 330